Sterculia Gum: Chemical Structure, Composition and Physico-Chemical Properties: A Review - Sharma, N.; Sinderpal, T. (Asian Journal of Chemistry, 2019)
Physico-chemical properties are crucial characteristics of hydrocolloids as they decide the applicability of them. Rheology of system, flow behaviour and mechanical properties make hydrocolloids suitable for food industry. Modification of consistency or texture properties of functional polymers also controls their sensory characteristics, thereby they become significant essences such as thickener, gelling agents, foaming agent, texture modifier, viscosifier, emulsifier, stabilizer and binder. Industrial and pharmaceutical applications are also controlled by some suitable physico-chemical properties of hydrocolloids. The polysaccharide gum exudates constitute a architecturally distinct class of complex biomacromolecules having unique physico-chemical properties. Due to their good bio/tissue compatibility, non-toxicity, they are extensively used in the field of tissue engineering, drug delivery and wound healing. Chemical and molecular architecture of hydrocolloids in turn controls their physico-chemical and functional properties. Sterculia gum is a substituted rhamnogalacturonoglycan (pectic) type exudate gum used as suspending agent, gelling agents, emulsifier, bulk laxative, dental adhesive, drug delivery agent and wound healing agent. It exhibits high water retention capacity, high viscosity and least solubility. Solutions of sterculia gum are viscoelastic and thixotropic. Sterculia gum has been recommended as effective wound dressing material as it can form a intensely adhesive gel when dispersed in minimum ammount of water. Owing to wide applications and distinctive properties of sterculia gum, present work is an endeavor to summarize the molecular organization, chemical configuration and physico-chemical properties of sterculia gum and the factors affecting physico-chemical properties of sterculia gum.